The Initial Reading Comprehension Profile of EFL Learners - Afi Normawati (English Education Department - Universitas Nasional Karangturi, 2021)
Reading is important in EFL learning since it helps learners build their language acquisition as well as obtain knowledge and information. The goal of reading is comprehension. To develop EFL leaners’ reading comprehension, reading strategy used should be carefully chosen; and the strategy should consider the initial comprehension profile of the learners. The paper reports a study at finding out the initial reading comprehension profile of EFL learners. The study was conducted in Universitas Nasional Karangturi involving first semester students of English Education Department taking Engagement Reading class. This is a descriptive research with mixed method design. The data were in the form of students’ scores collected by using reading test taken from Cambridge IELTS Academic Reading test. The data were then analysed by using statistical analysis. The study shows that the students’ mean score is 4, which means they are at A2 level of English according to Common European Framework of Reference for Languages (CEFR). The students at this level are able to comprehend simple texts about issues that are familiar with language related to everyday activities with high-frequency words. Furthemore, based on the students’ performance on each component of IELTS reading test, the study indicates that the students get the highest score on the component of reading for details (33.8%). It means that the students are at the literal level of reading comprehension